Effect of Birthweight, Illness History, and Dietary Pattern, on the Incidence of Anemia in Children Under-Five at Tasikmadu Health Center, Karanganyar, Central Java - Anggraini, Yeni; Salimo, Harsono; Tamtomo, Didik (Journal of Maternal and Child Health, 2017)
Background: The first five years of life is often regarded as